2015
DOI: 10.1590/1516-1439.310114
|View full text |Cite
|
Sign up to set email alerts
|

Electrospinning of Gelatin/Poly (Vinyl Pyrrolidone) Blends from Water/Acetic Acid Solutions

Abstract: Electrospinning is a versatile and efficient technique for obtaining polymeric microfibers and nanofibers with great potential for applications in tissue engineering, biosensors, filtration, wound dressings, controlled drug release and enzyme immobilization. Electrospun fibers are obtained by applying an electric field in a polymer solution resulting in non-woven fibrous mats with high surface area relative to volume and high porosity. In this work, the electrospinning of gelatin/poly(vinyl pyrrolidone) (PVP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(42 citation statements)
references
References 38 publications
5
35
0
1
Order By: Relevance
“…The initial weight loss at temperature of less than 150 °C was due to the evaporation of solvent and any moisture from the nanofibre. This result is similar to the findings of Kim et al [52] and Sales et al [53]. At the temperature range from 373 °C to 466 °C, another significant weight loss of 71.5% was detected in the graph, which is associated with the thermal decomposition of the main chain PVP polymer [52].…”
Section: Resultssupporting
confidence: 91%
“…The initial weight loss at temperature of less than 150 °C was due to the evaporation of solvent and any moisture from the nanofibre. This result is similar to the findings of Kim et al [52] and Sales et al [53]. At the temperature range from 373 °C to 466 °C, another significant weight loss of 71.5% was detected in the graph, which is associated with the thermal decomposition of the main chain PVP polymer [52].…”
Section: Resultssupporting
confidence: 91%
“…We observed that only mats produced from 17% w/w aqueous PVP had acceptable reproducibility, with mats formed by smooth fibres (Figure 1(a)) of well-defined size distribution with an average fibre size of 290 ± 50 nm (Figure 1(g,h)). Indeed, the rheological measurements indicated that 17% w/w PVP solution (Figure 1(f)) has sufficiently high viscosity (η) at the shear rates that match flow rates used during electrospinning process, and agrees with values reported by others [41]. Furthermore, it can be seen that the 17% PVP solution exhibits shear-thinning behaviour in the used shear rate regime (1-100 s -1 ), which is a critical condition for higher-viscosity solutions to be electrospun [42].…”
Section: Resultssupporting
confidence: 89%
“…These improved properties were attributed to the electrostatic interaction and hydrogen bonding between the amino polysaccharide and gelatin [ 54 , 55 ]. Foam [ 56 ], 3D printed substrates [ 57 , 58 ], electrospinning [ 59 ], phase separation [ 60 ], porogen leaching [ 61 ], freeze-drying [ 62 ] and textile structures [ 63 ] are methods that have been used to prepare scaffolds from biodegradable blends or composites, for biomedical applications.…”
Section: Introductionmentioning
confidence: 99%